NETWORKING WITH NEW TECHNOLOGIES IN TRAINING OF SCIENCE TEACHERS: A CASE STUDY FROM THE LAYOUT TO THE REFLECTION - KALATHAKI, Maria (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The Major Teachers’ Training Program (MTTP) implemented at pilot phase in 2009-2011 by the Greek Pedagogical Institute for teachers of Primary and Secondary Education in five regions of Greece, among them was Mytilene. The program was based on the findings of a survey of the teachers’ training needs and focused on the development of flexible training models, such as e-learning, mixed in person and remotely communication, synchronous and asynchronous education etc., by involving new technologies in all school objects. In this paper, the trainer describes the exploitation of New Technologies and Social Networking Web 2.0 in a target based, sustainable and integrative Major Teachers’ Training Program (MTTP) at Mytilene. In the training process involved in person and remotely, synchronous and asynchronous encounters of trainees and trainers with Moodle platform for producing Internet-based courses, a blogspot for information, communication and exchange of views and ideas as well as two wikispaces websites for co-formulation of educational material concerning parallel of MTTP activities in local issues “Aristotle and Lesvos” and “Sappho the Educator". Additionally, in the communication contributed emails, skype and telephones. Networking aimed at managing a large volume and consumption of variety of training materials, applying and practicing of innovative methodology for personal and professional development of teachers with consequent improvement of the education provided to their students. The whole project served the strategic objective of the Greek Ministry of Education “New School”, with emphasis on the development of horizontal competences of teachers and students, which run across all school subjects and are required in everyday educational practice.